2013
DOI: 10.1590/s1679-87592013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency physical variations in the coastal zone of Ubatuba, northern coast of São Paulo State, Brazil

Abstract: Sea level (SL), wind, air temperature (AT) and sea surface temperature (SST) variations in the coastal region of Ubatuba, northern coast of São Paulo, are assessed. A Lanczos-square cosine filter, with a 40-hour window, was applied over the SL time series between 1978 and 2000, except for the period comprising 1984 to 1986. In order to study subtidal effects on mean sea level (MSL), SL numerical filtering indicated that there was a virtually complete removal of semidiurnal and diurnal astronomical tidal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Populations of C. bisinuatus along the São Paulo coastline exhibit a very clear fortnightly rhythm of larval release (Bueno et al 2010). In the study area, average sea surface temperature exhibits the lowest values in July, 21.9°C, and the highest in February, 28.6°C (Valentim et al 2013). The São Sebastião Channel is a meso‐oligotrophic system year‐round (Leal et al 2018).…”
Section: Methodsmentioning
confidence: 95%
“…Populations of C. bisinuatus along the São Paulo coastline exhibit a very clear fortnightly rhythm of larval release (Bueno et al 2010). In the study area, average sea surface temperature exhibits the lowest values in July, 21.9°C, and the highest in February, 28.6°C (Valentim et al 2013). The São Sebastião Channel is a meso‐oligotrophic system year‐round (Leal et al 2018).…”
Section: Methodsmentioning
confidence: 95%
“…It should be noted that there are quite a large number of papers on monitoring sea level changes near coasts in different areas of the World Ocean, for example, [Pérez Gómez et al, 2022;Valentim et al, 2013;Williams, 2013] but the observations obtained from these studies are used to analyze coastal erosion or to monitoring sea level changes associated with climate change and possible coastal flooding. In the recent paper [Koohestani et al, 2023] the authors analyzed the appearance of internal solitary waves in the Bay of Oman caused different mechanisms including variations of atmospheric pressure, wind, currents, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the Brazilian coast and especially in the coast of the state of Rio Grande do Sul (RS), there is a lack of long-term oceanographic data (Costa and Möller, 2011;Zavialov et al, 2002). Studies on SL at tidal and sub-tidal frequencies using field data are not found in the literature (Valentim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%